Detection of X-Ray Polarization in the Hard State of IGR J17091-3624: Spectropolarimetric Study with IXPE and NuSTAR Data - Dipak Debnath; Subham Srimani; Hsiang-Kuang Chang (The Astrophysical Journal)
The class-transition Galactic X-ray binary IGR J17091–3624 was simultaneously monitored by the Imaging X-ray Polarimetry Explorer (IXPE) and NuSTAR satellites. We present a detailed spectropolarimetric study of the source using data from both satellites covering the period from 2025 March 7 to 10. A polarimetric analysis in the 2–8 keV band using a model-independent method reveals a significant detection of polarization degree (PD) of (11.3 ± 2.35)% at a polarization angle (PA) of $82\mathop{.}\limits^{^° }7± 5\mathop{.}\limits^{^° }96$ (significant at >4 σ ). The model-dependent polarization analysis using the polconst and polpow models yields consistent values of PD and PA. In both methods, an energy-dependent increasing trend of PD is observed. In the 6–8 keV band, a maximum PD of (29.9 ± 8.46)% (significant at >3 σ ) is detected at a PA of 88 $\mathop{.}\limits^{\unicode{x000b0}}$ 0 ± 8 $\mathop{.}\limits^{\unicode{x000b0}}$ 15 (>3 σ ). The joint spectral analysis using IXPE and NuSTAR data in the 2–70 keV band was performed with four different sets of phenomenological and physical models. Our results indicate a strong dominance of nonthermal photons originating from a “hot” Compton cloud, suggesting that the source was in a hard spectral state. Spectral fitting with the physical kerrbb and TCAF models provides an estimate of the black hole mass ${M}_{{\rm{BH}}}=14.{8}_{-3.4}^{+4.7}\,M_{\odot }$ and dimensionless spin parameter a ^* ∼ 0.54. The requirement of a higher hydrogen column density in the spectral fit of the second NuSTAR observation is attributed to the obscuration of nonthermal photons during the dip phase, likely caused by the presence of wind accreted from the companion star.